A cross-sectional study on knowledge, attitude and practice regarding rabies among patients attending a tertiary care centre, Solapur Maharashtra - Roy, Payel; Nandimath, Viresh A.; Bhadake, Kavita H. (International Journal Of Community Medicine And Public Health, 2023)
Background: Rabies is a neglected zoonotic tropical disease. Rabies is one of the world’s deadliest diseases which has 100% fatality and at the same time 100% preventable. The present study is an attempt to assess the knowledge, attitude and practice regarding rabies among animal bite patients and sociodemographic factors associated with it. Methods: This observational cross-sectional study was done in a tertiary care centre, Solapur after taking IEC approval during 1st October 2022 to 31st October 2022, among all adult patients (≥18 years age) attending anti-rabies OPD, in a pre-tested, structured, questionnaire. Results: Among 194 participants 51 (26.29%), 101 (52.06%) and 42 (21.65%) of participants had high, moderate and low knowledge regarding rabies respectively; 75 (38.66%), 106 (54.64%) and 13 (6.7%) had high, moderate and low attitude towards rabies respectively; 160 (82.47%), 33 (17.01%) and 1 (0.52%) had high, moderate and low practice towards rabies prevention and control respectively. In this study knowledge is significantly associated with age, family size, education and socio-economic status; attitude is significantly associated with education and practice is significantly associated with family size. Conclusions: Majority of the participants (101) had moderate knowledge regarding modes of transmission of rabies, fatality of rabies, symptoms of rabid animal, incubation period of rabies and PEP after animal bite, etc. Most of the participants (106) had moderate attitude towards completion of Inj. ARV schedule and the necessity to promote knowledge about rabies in the community. Majority of the participants (160) had high practice regarding first aid after animal bite and anti-rabies vaccination.